TELEPRACA JAKO PRZEDMIOT POROZUMIENIA RAMOWEGO Z DNIA 16 LIPCA 2002 R. - Karbowska, Sylwia (Zeszyty Prawnicze, 2017)
Telework as the Subject of the Framework Agreement Dated 16 July 2002 Summary This article deals with the rules of conducting a telework that were approved by the social partners at the European Union level in a form of an autonomous agreement. The first chapter describes the recent changes in work environment, including a dynamic development of modern information and telecommunication technologies, which have enabled an introduction of more flexible solutions to the organization of work a telework being one of them. It shows the circumstances in which the idea of a telework emerged as well as the increase in its popularity in the world. The second chapter covers the historical background of concluding the Framework Agreement on a telework in the light of the social dialogue development at the level of European Union’s institutions. The consultancy procedure for the social partners defined in the articles 137-139 of the Treaty Establishing the European Community was mentioned as the basis for concluding the autonomous agreements. The legal status of the Framework Agreement is also clarified therein. The third chapter describes the solutions adopted by the Framework Agreement, including a definition of a telework incorporating its internal differentiation, features of teleworking as well as the rules of conducting the telework according to European social partners. In the final chapter, the author raised the issue of implementing the rules of the Framework Agreement in selected countries of the European Union and emphasised the difficulties that have emerged.